ABOUT SARCOMA RETROPERITONEAL CASE AND PREGNANCY, DEPARTMENT OF GYNECOLOGY AND OBSTETRICS OF THE HOSPITAL MOTHER CHILD "SAN BARTOLOME" - Bernedo B., Hernán (2015)
Considering the rarity of solid tumors and pregnancy pelvis in literature states; 1 in 10,000 pregnancies, and the much lower frequency of ovarian, 2 to 3% of ovarian tumors found during pregnancy cancer; is extremely interesting for its rarity increased the presence of a retroperitoneal sarcoma with pelvic extension coinciding with gestaci6n, even if this sarcoma is a malignant Schwamoma, as has been listed in the Department of Pathology of our hospital.